(3GdchGcH GdOQjI aj GdfUhU Ydi EeGeI NjQ GdHQjI hPcQ fLGI CJHGY GdPQjIs - (3UdGM Hf EHQGgje Hf CMeO Hf GdgGOj Gdj GdMbs
(3ChdgG (B:s
(3GdMeO ddg GdPi ENJGQ Bd eMeO Ydjge GdSdGe Ydi Yde Ydi GdYGdejf ,hEaJQV ehOJge Ydi cGag Ndbg CLejYf s
(3BNQgG (B:s
(3aef EgJOi aEfeG jgJOi dfaSg , hef Vd aEfeG Vd YdjgG , heG QHc HXdGe ddYHjO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3eLGejY (B87) s
Keywords: (3GdJhMjO hGdedd hGdfMds